Acute Urinary Retention - Silva de Lima, Douglas; Manzi, Joao; Abreu, Phillipe; Agostinho, Aparecido Donizeti [UNESP]; Jesus, Carlos Márcio Nóbrega de [UNESP]; Trindade Filho, José Carlos Souza [UNESP]; Slongo, Julio (Springer Nature, 2025)
Acute urinary retention (AUR) is the inability to void voluntarily, usually associated with suprapubic discomfort and pain, in a patient with a full bladder. It is the most common urological emergency. In adults, AUR can be triggered by obstructive, neurological, traumatic, infectious, inflammatory, and pharmacological causes (Tables 79.1 and 79.2). In children, the main causes of acute urinary retention are phimosis, urethral meatus stenosis, posterior urethral valve, bladder stone, neurogenic bladder (mainly meningomyelocele), and ureterocele.